The Importance of Principal's Strategy in Improving Literacy and Numeracy Skills of Students at SMP Negeri 3 Waingapu - Lapir, Corlina Niwa; Karwanto, Karwanto; Sholeh, Muhammad (Universitas Pahlawan Tuanku Tambusai, 2025)
Literacy and numeracy skills are important foundations in education that determine the success of students in facing future challenges. Literacy includes the ability to read, write, and understand information, while numeracy involves logical and critical thinking skills in solving mathematical problems. Principals, as educational leaders, play a crucial role in improving these two skills through effective strategies. The results of this study discuss the importance of the role of principals in building a culture of literacy and numeracy, improving teacher competence, using technology, involving parents and the community, and conducting monitoring and evaluation. This study uses qualitative methods to analyze the strategies implemented by principals in improving literacy and numeracy. The place that is the object of the study is SMP Negeri 3 Waingapu, East Nusa Tenggara. With the right strategy, principals can create a learning environment that supports improving student literacy and numeracy. Thus, it can produce graduates who have critical thinking skills and can compete globally.